Architecture of craft and service centers by Ranko Radović – creating an urban ambience - Antešević, Nebojša; Gubić, Ilija (Arhitektura i urbanizam, 2023)
Ranko Radović (1935-2005) was a prominent Serbian, Montenegrin and Yugoslavian architect, urban planner and designer, professor and architecture historian and theorist. This paper explores the architectural concepts and urban characteristics of the craft and service centers he designed, which were built in Belgrade (1968-1972), Šabac (1982) and Ljig (1988), as well as his architectural-urban planning research proposal for the reconstruction and revitalization of the old market and the area under the bastion of the fortress in Novi Pazar (1986-1987). In addition to his notable designs for the Sutjeska Battle Memorial House (Bosnia and Herzegovina), the town hall in Aranđelovac, the Partizanka hotel, a post office and a bank in Vrnjačka Banja, and the reconstruction of the Atelje 212 theater in Belgrade (Serbia), Radović’s solutions for craft and service centers in Belgrade, Šabac and Ljig represent specific considerations of architecture and urbanity, in which the experiences of modernism, critical regionalism, and the influences of postmodernism are sublimated. He also produced a proposal, partly implemented, for the protection and revitalization of the old bazaar market in Novi Pazar, with a grouping of low-rise buildings for craft and service purposes and prefabricated-temporary structures based on the traditional scale. As a contribution to the study of Ranko Radović’s work, these specific micro-urban structures are analyzed in the context of his theoretical views on contemporary architecture, urbanism and tradition, and the aim of the work is to illuminate and document Radović’s contribution to the ideas of the development of modern architecture and cities in Serbia. Due to the architectural concepts and urbanistic values of craft-service centers expressed in the ideas of ephemerality and changeability, the paper provides an analytical overview and photo-documentation of their existing state, and the possibilities of their revitalization are discussed.